Mitochondrial protein 18 is a positive apoptotic regulator in cardiomyocytes under oxidative stress. (9th May 2019) - Aung, Lynn H.H.; Li, Yu-Zhen; Yu, Hua; Chen, Xiatian; Yu, Zhongjie; Gao, Jinning; Li, Peifeng
Abstract : Accumulation of reactive oxygen species is a common phenomenon in cardiac stress conditions, for instance, coronary artery disease, aging-related cardiovascular abnormalities, and exposure to cardiac stressors such as hydrogen peroxide (H2 O2 ). Mitochondrial protein 18 (Mtp18) is a novel mitochondrial inner membrane protein, shown to involve in the regulation of mitochondrial dynamics. Although Mtp18 is abundant in cardiac muscles, its role in cardiac apoptosis remains elusive. The present study aimed to detect the role of Mtp18 in H2 O2 -induced mitochondrial fission and apoptosis in cardiomyocytes. We studied the effect of Mtp18 in cardiomyocytes by modulating its expression with lentiviral construct of Mtp18-shRNA and Mtp18 c-DNA, respectively. We then analyzed mitochondrial morphological dynamics with MitoTracker Red staining; apoptosis with terminal deoxynucleotidyl transferase-mediated dUTP nick-end-labeling (TUNEL) and cell death detection assays; and protein expression with immunoblotting. Here, we observed that Mtp18 could regulate oxidative stress- mediated mitochondrial fission and apoptosis in cardiac myocytes. Mechanistically, we found that Mtp8 induced mitochondrial fission and apoptosis by enhancing dynamin-related protein 1 (Drp1) accumulation. Conversely, knockdown of Mtp18 interfered with Drp1-associated mitochondrial fission and subsequent activation of apoptosis in both HL-1 cells and primary cardiomyocytes. However, overexpression of Mtp18 alone was not sufficient to execute apoptosis when Drp1 was minimally expressed, suggesting that Mtp18 and Drp1 are interdependent in apoptotic cascade. Together, these data highlight the role of Mtp18 in cardiac apoptosis and provide a novel therapeutic insight to minimize cardiomyocyte loss via targetting mitochondrial dynamics.